2003
DOI: 10.1042/cs1040389
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial sodium channel (ENaC) subunit mRNA and protein expression in rats with puromycin aminonucleoside-induced nephrotic syndrome

Abstract: In experimental nephrotic syndrome, urinary sodium excretion is decreased during the early phase of the disease. The molecular mechanism(s) leading to salt retention has not been completely elucidated. The rate-limiting constituent of collecting duct sodium transport is the epithelial sodium channel (ENaC). We examined the abundance of ENaC subunit mRNAs and proteins in puromycin aminonucleoside (PAN)-induced nephrotic syndrome. The time courses of urinary sodium excretion, plasma aldosterone concentration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
7
2
Order By: Relevance
“…Thus this is likely to represent a key molecular basis for the sodium retention associated with PAN-induced nephrotic syndrome combined with the previously demonstrated increase in collecting duct Na-K-ATPase activity and protein abundance (13, 14). Thus our studies extend a previous study demonstrating that the total kidney abundance of ENaC subunits was not downregulated but maintained (3). Moreover, the present results extend this study by demonstrating the segmental specific upregulation of all three ENaC subunits, and most importantly, provide evidence for a significantly increased apical targeting by immunoelectron microscopy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus this is likely to represent a key molecular basis for the sodium retention associated with PAN-induced nephrotic syndrome combined with the previously demonstrated increase in collecting duct Na-K-ATPase activity and protein abundance (13, 14). Thus our studies extend a previous study demonstrating that the total kidney abundance of ENaC subunits was not downregulated but maintained (3). Moreover, the present results extend this study by demonstrating the segmental specific upregulation of all three ENaC subunits, and most importantly, provide evidence for a significantly increased apical targeting by immunoelectron microscopy.…”
Section: Discussionsupporting
confidence: 80%
“…Thus this study directly points to a role of increased sodium reabsorption in the collecting duct and, hence, it may be hypothesized that dysregulation of the key sodium channels and transporters in the collecting duct may be responsible for this. A few studies subsequently demonstrated that sodium retention in PAN nephrotic rats is correlated with increased Na-K-ATPase activity and expression in the cortical collecting duct (CCD) (13,14), and a recent study demonstrated no major changes in the protein abundance of the epithelial sodium channel (ENaC) subunits in whole kidney (3).…”
mentioning
confidence: 99%
“…Whether membrane recruitment of ENaC is associated with de novo synthesis of channel units remains difficult to address in vivo, in the absence of protein metabolic labeling. At variance with a previous report (11), our results show an increased level of ␤-ENaC mRNA in CCD from PAN-nephrotic rats. At the protein level, there are also discrepancies in the literature as Audigé et al (11) reported increased amounts of ␣-ENaC and no change in ␤-and ␥-ENaC in the kidney cortex of PAN-nephrotic rats, whereas Kim et al (3) described no change in ␣-and ␤-ENaC abundance and an increase of ␥-ENaC.…”
Section: Discussioncontrasting
confidence: 56%
“…At variance with a previous report (11), our results show an increased level of ␤-ENaC mRNA in CCD from PAN-nephrotic rats. At the protein level, there are also discrepancies in the literature as Audigé et al (11) reported increased amounts of ␣-ENaC and no change in ␤-and ␥-ENaC in the kidney cortex of PAN-nephrotic rats, whereas Kim et al (3) described no change in ␣-and ␤-ENaC abundance and an increase of ␥-ENaC. From these data, it can be concluded that recruitment of pre-existing ENaC is the main cause of increased ENaC activity in PAN nephrosis.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation